Social movements that exchange information and learn from each other: Plaza Podemos and the PAH school - Sanz-Martos, Sandra (Anuario ThinkEPI, 2015)
Social movements based on collective intelligence are consolidating and adding participants. Information exchange and management, as well as collaborative learning , are identified as key to success. Plaza Podemos and the PAH school (for people facing mortgage foreclosure: Plataforma de Afectados por la Hipoteca) are two good examples.